Talent management practice and retention of employees in pharmaceutical firms in Nairobi County in Kenya - Nyongesa, Wesonga Justus; Westhuizein, Johan Van Der (International Journal of Innovative Research and Scientific Studies, 2025)
The contemporary business environment is characterized by competition, with organizations encountering challenges related to employee retention, irrespective of their size or sector. Effective talent management is essential for organizations to acquire the requisite skills and expertise to fulfill their operational requirements. Retention of skilled employees is essential for maintaining competitive advantages. This research investigates the impact of talent management practices on employee retention in pharmaceutical companies located in Nairobi County, Kenya. Theoretical frameworks encompass resource-based view theory. The research focused on 58 agrochemical firms registered with the Agrochemicals Association of Kenya, specifically targeting management-level employees, amounting to a total of 324 individuals. The sample size of 179 respondents was calculated using the Krejcie and Morgan formula, employing stratified random sampling. Data collection utilized structured questionnaires, while quantitative analysis incorporated inferential and descriptive statistics, including means, standard deviations, frequencies, and percentages. Correlation analysis evaluated the relationship between talent development and employee retention, whereas multiple regression determined the effect of talent management practices. The research indicates that talent development has a positive impact on employee retention within pharmaceutical firms located in Nairobi County. Recommendations involve enhancing talent development strategies and cultivating a supportive work environment to improve employee retention rates.